Physiology and interaction of nitrate and nitrite reduction in Staphylococcus carnosus. - Neubauer, H (1996)
Staphylococcus carnosus reduces nitrate to ammonia in two steps. (i) Nitrate was taken up and reduced to nitrite, and nitrite was subsequently excreted. (ii) After depletion of nitrate, the accumulated nitrite was imported and reduced to ammonia, which again accumulated in the medium. The localization, energy gain, and induction of the nitrate and nitrite reductases in S. carnosus were characterized. Nitrate reductase seems to be a membrane-bound enzyme involved in respiratory energy conservation, whereas nitrite reductase seems to be a cytosolic enzyme involved in NADH reoxidation. Syntheses of both enzymes are inhibited by oxygen and induced to greater or lesser degrees by nitrate or nitrite, respectively. In whole cells, nitrite reduction is inhibited by nitrate and also by high concentrations of nitrite (> or = 10 mM). Nitrite did not influence nitrate reduction. Two possible mechanisms for the inhibition of nitrite reduction by nitrate that are not mutually exclusive are discussed. (i) Competition for NADH nitrate reductase is expected to oxidize the bulk of the NADH because of its higher specific activity. (ii) The high rate of nitrate reduction could lead to an internal accumulation of nitrite, possibly the result of a less efficient nitrite reduction or export. So far, we have no evidence for the presence of other dissimilatory or assimilatory nitrate or nitrite reductases in S. carnosus.